3D Printing Manufacturing Techniques, Materials, and Applications: An Overview. (10th December 2021) - Srinivasan, D.; Meignanamoorthy, M.; Ravichandran, M.; Mohanavel, V.; Alagarsamy, S. V.; Chanakyan, C.; Sakthivelu, S.; Karthick, Alagar; Prabhu, T. Ram; Rajkumar, S.
Abstract : 3D printing, also called additive manufacturing (AM), is a method of creating 3D solid parts from a digital document. By utilizing additive routes, the fabrication of 3D-printed objects can be made. These layers can be viewed as a gently cut level cross-area of the manifest object. 3D printing is somewhat in obstruction to subtractive manufacture, which is expelling/discharging out a touch of metal or plastic for the occurrence of a milling machine. 3D printing authorizes creating multifarious profiles employing fewer materials than conventional fabrication systems. This review article provides the general idea of 3D printing production techniques, materials used, and applications in the aircraft and automobile industry and biomedical fields.